Lateral Impact of Travelling Fires on Structural Elements in Large Compartments: Insights from Test 1 - Naveed Alam; Ali Nadjai (Fire, 2025)
The expansion of unobstructed floor plans has resulted in large open areas, especially in modern designs. Although these new designs are appealing and esthetically attractive, they remain at a risk of large fires which may initiate at certain location(s) and make their way along to the other parts of the compartment. Such fires are called travelling fires and are not currently covered by the design codes due to lack of available research and understanding. Unlike traditional compartment fires, travelling fires may last longer and may result in compromising the structural integrity due to prolonged fire exposure. This article studies the impact of travelling fires on structures with focus on the structural elements, oriented perpendicular to the direction of fire travel. The data presented comes from Test 1, conducted by the authors as part of the TRAFIR project at Ulster University. The details provided include the recorded gas temperatures within the compartment and the temperatures recorded in the surrounding structural elements, along gridlines ② and ③. The test compartment consisted of a steel structure with a hollow core concrete roof. The structural steelwork was supplied with additional dummy columns for data acquisition purposes. The study demonstrates that structural elements located within the fuel bed are subjected to significantly higher temperatures. The gas temperature differences within and outside the fuel bed on occasions exceed 450 °C across compartment width, while the same for columns and beams were up to 350 °C and 200 °C, respectively. Such transient heating of the structure could possibly induce the load distribution within the structure and may help achieve improved global fire resistance. The findings from this study will improve our understanding of travelling fires, their impact on structures, and will open directions to study the collapse mechanisms of structures under the influence of travelling fires and will help with devising design guidance for structures exposed to travelling fires.